PHYSICAL AND MECHANICAL PROPERTIES OF ROYAL PALM (Roystonea regia (Kunth O.F.Cook) as a COMPOSITE REINFORCING MATERIAL - Adzkia, Ulfa; Hasanuddin, Hasanuddin; Nugroho, Naresworo; Karlinasari, Lina (Universitas Gorontalo, 2025)
The Royal Palm (Roystonea regia) is a type of monocotyledonous plant that is widely planted, especially as an ornamental plant that is part of the urban landscape. However, in its growth, there is a natural cycle where the royal palm leaves will fall and end up as waste. In this case, the royal palm leaf sheath is thought to have potential as a composite reinforcement material. However, in its utilization as a composite reinforcement material, basic information such as the physical and mechanical characteristics of the material needs to be known. The purpose of this study was to evaluate the physical and mechanical properties and potential utilization of the royal palm leaf sheath. The research shows that the green royal palm leaf sheath's water content and density are higher than the brown leaf sheath. In addition, the dimensional stability of the green leaf sheath is higher than that of the brown leaf sheath. The tensile strength of the green conditions is lower than that of the brown conditions, and the strength decreases towards the core of the royal palm leaf sheath. Meanwhile, the tensile strength of the fibers from the two leaf sheath conditions is not significantly different. This test shows that the royal palm leaf sheath fiber is classified into fiber class II. This shows that the royal palm leaf sheath has the potential as a composite reinforcement material.